Housing difficulties, health status and life satisfaction - Hu, Mingzhi; Su, Yinxin; Yu, Xiaofen (Frontiers in Psychology, 2022)
This study examines the effects of housing difficulties on life satisfaction. By using longitudinal data from the China Family Panel Studies survey, we find strong evidence that households who experience housing difficulties are less satisfied with their lives than those who do not after controlling for a wide range of household demographic and socioeconomic characteristics and county and year fixed effects. Our estimated results are robust to unobservable household characteristics, model misspecification and selection bias. We also provide explanations for the negative effects of housing difficulties on life satisfaction through which housing difficulties are detrimental to physical and psychological health. Life satisfaction remains negatively associated with housing difficulties even after controlling for health status.